Analysis of Inflation in Indonesia: The Role of Money Supply, Interest Rate, Imports, Exports and Exchange Rate - Firmansyah, Arif Amanudin; Tartila, Tazkia Fitri Nur (Journal of Policy and Sustainable Development Studies, 2026)
Inflation is one of the macroeconomic problems that must be addressed in measuring the economic stability of a country. The purpose of this study is to determine how the amount of money in circulation, interest rate, imports, exports, and exchange rate affect inflation in Indonesia from 2015 to 2024. This study uses secondary data obtained from the Central Statistics Agency (BPS), Ministry of Trade (Kemendag) and Bank Indonesia (BI). To achieve the research objectives, data analysis uses multiple linear regression methods. The result shows that money supply and imports have a negative but significant effect on inflation. However, exports have a positive and significant effect on inflation. Meanwhile, exchange rate has a positive but insignificant effect on inflation. Policy makers, especially those who implement monetary policy, must be careful with the impact of the amount of money in circulation, interest rate, imports, exports and exchange rate that can affect inflation.